Poverty Measurement in the Era of Food Away from Home Testing Alternative Approaches in Vietnam - Farfan, Gabriela (World Bank E-Library Archive, 2019)
Food consumed outside the home in restaurants or other food establishments is a growing segment of consumption in many developing countries. However, the survey methods that are utilized to collect data on expenditures on food away from home are often simplistic and could potentially result in inaccurate reporting. This study addresses the potential inaccuracy of commonly used methods and tests potentially superior methods to inform best practices when collecting data on consumption of food away from home. A household survey experiment was implemented in Hanoi, Vietnam, to test these different methods. Using a food away from home consumption diary as a benchmark, the study finds that many of the alternative methods considered-including asking about consumption in one line (the existing practice in Vietnam) or asking each individual about their food away from home-lead to underreporting (33 and 22 percent underestimates, respectively). Surprisingly, using one respondent and helping them with recall with a simple worksheet as well as bounding (two-visits) results in food away from home estimates that are indistinguishable from those reported in the benchmark diary. This finding implies that there is a more cost-effective way to collect accurate data on food away from home than an intensive daily diary. Furthermore, it highlights the inaccuracy associated with collecting data on consumption of food away from home from a single question in a survey. Although limited analysis can be conducted on the implications for poverty, the study finds that the profiles of the poorest households differ across different methods of collecting information on food consumed away from home